2022
DOI: 10.1029/2021jd036007
|View full text |Cite
|
Sign up to set email alerts
|

The Mid‐ to High‐Latitude Migrating Semidiurnal Tide: Results From a Mechanistic Tide Model and SuperDARN Observations

Abstract: Atmospheric tides are global-scale waves whose periods are an integer fraction of a solar day (Chapman & Lindzen, 1970). The tides are forced primarily by radiative and latent heating effects in the lower atmosphere (Hagan, 1996), but obtain their largest amplitudes in the mesosphere-lower-thermosphere (MLT) region (80-120 km altitude). There they are expressed as pronounced oscillations in a broad range of atmospheric fields, such as density, pressure, and wind. The migrating tides are those tides which follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…(2021) and van Caspel et al. (2022) found that the seasonality of SW2 in the middle to high latitudes can be explained by the background atmosphere’s distortion of SW2 modes originating from the stratosphere. However, these do not mean that our results contradict with their results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2021) and van Caspel et al. (2022) found that the seasonality of SW2 in the middle to high latitudes can be explained by the background atmosphere’s distortion of SW2 modes originating from the stratosphere. However, these do not mean that our results contradict with their results.…”
Section: Discussionmentioning
confidence: 99%
“…These suggested mechanisms for the seasonality of SW2 in the tropics are very different from the suggested mechanisms for the seasonality of SW2 in the middle to high latitudes. Pedatella et al (2021) and van Caspel et al (2022) found that the seasonality of SW2 in the middle to high latitudes can be explained by the background atmosphere's distortion of SW2 modes originating from the stratosphere. However, these do not mean that our results contradict with their results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations